Gestão de conflitos no relacionamento entre franqueadores e franqueados: estudo de caso - Bernardino, Eliane de Castro (2002)
The present dissertation studies the conflict in the relationship among franchisors and franchisees. A theoretical reference is presented, where franchisingfits in the marketing channels framework, as well as the most relevant causes that give rise to conflicts among franchisors andfranchisees and their existing solutions. Also, in this dissertation, the results ofan exploratory research are presented, focusing on retail franchise network. In this case study, we try to show and discuss how its members preveni and manage conflicts that arise within the franchisor-franchisee relationship.